(untitled) (Vietnam Journal of Community Medicine, 2025)
Objectives: To assess the antipyretic supportive and the side effects of auricular acupressure in children with virus fever. Method: Clinical trial study, comparison before and after treatment’s result and compare with control group. 60 patients were divided into 2 equal group: the study group were administered auricular acupressure combined with general treatment, the control group were administered general treatment. Results: After treatment, the average fever duration of the study group is 31.31 ± 24.61 (hour), lower than that of the control group (p < 0.05). The number of times taking fever reducer medicine, in study group is 3.85 ± 2.01 (times), lower than that of the control group (p < 0.05). Auricular acupressure did not cause side effects on clinical. Conclusion: Auricular acupressure was effective in reducing fever and no side effects on clinical.